Originally Posted by
alreadyinuse I got stuck on these on my homework, and was hoping someone could help be out.
1. ysqrt(1-x^2)y' - xsqrt(1-y^2) = 0 Mr F says: $\displaystyle y \, \sqrt{1 - x^2} \, \frac{dy}{dx} = x \sqrt{1 - y^2} \Rightarrow \frac{y}{\sqrt{1 - y^2}} \, dy = \frac{x}{\sqrt{1 - x^2}} \, dx $ ......
Initial condition is y(0) = 1
2. dr/ds = e^(r+s) Mr F says: Writing $\displaystyle e^{r + s} = e^r e^s$ might make the DE more obviously seperable to you .....
Initial condition is r(1) = 0
Thanks!